PENGARUH ORGANIZATIONAL CULTURAL LEADERSHIP DAN TEAMWORK TERHADAP EMPLOYEE PERFORMANCE DENGAN ORGANIZATIONAL COMMITMENT SEBAGAI VARIABEL INTERVENING - Arisanti, Andini Ulima; Nasution, Juliana; Rahma, Tri Inda Fadhila (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.12.TAHUN.2024DO - 10.24843/EEB.2024.v13.i12.p02, 2024)
This study aims to examine the effect of Organizational Cultural Leadership and Teamwork on Employee Performance with Organizational Commitment as an intervening variable. Rapid organizational development requires a deep understanding of the factors that influence Employee Performance. One important factor considered in this study is Organizational Cultural Leadership, which can shape values, norms, and behaviors that influence individual motivation and performance. In addition, teamwork is also believed to play an important role in achieving organizational goals. Organizational Commitment is hypothesized as a connecting factor that can strengthen the influence of both variables on Employee Performance. This study uses a quantitative approach with path analysis techniques to test the relationship between variables. The results show that Organizational Cultural Leadership and Teamwork have a significant influence on Employee Performance, both directly and through Organizational Commitment. These findings provide practical implications for managers and organizational leaders to pay more attention to developing an organizational culture that supports effective Leadership and solid team collaboration, which can ultimately improve Organizational Commitment and Employee Performance.